SENP1, but not fetal hemoglobin, differentiates Andean highlanders with chronic mountain sickness from healthy individuals among Andean highlanders - Hsieh, Matthew M. (Exp Hematol, 2016)
Chronic mountain sickness (CMS) results from chronic hypoxia. It is unclear why certain highlanders develop CMS. We hypothesized that modest increases in fetal hemoglobin (HbF) are associated with lower CMS severity. In this cross-sectional study, we found that HbF levels were normal (median = 0.4%) in all 153 adult Andean natives in Cerro de Pasco, Peru. Compared with healthy adults, the borderline elevated hemoglobin group frequently had symptoms (headaches, tinnitus, cyanosis, dilatation of veins) of CMS. Although the mean hemoglobin level differed between the healthy (17.1 g/dL) and CMS (22.3 g/dL) groups, mean plasma erythropoietin (EPO) levels were similar (healthy, 17.7 mIU/mL; CMS, 12.02 mIU/mL). Sanger sequencing determined that single-nucleotide polymorphisms in endothelial PAS domain 1 (EPAS1) and egl nine homolog 1 (EGLN1), associated with lower hemoglobin in Tibetans, were not identified in Andeans. Sanger sequencing of sentrin-specific protease 1 (SENP1) and acidic nuclear phosphoprotein 32 family, member D (ANP32D), in healthy and CMS individuals revealed that non-G/G genotypes were associated with higher CMS scores. No JAK2 V617F mutation was detected in CMS individuals. Thus, HbF and other classic erythropoietic parameters did not differ between healthy and CMS individuals. However, the non-G/G genotypes of SENP1 appeared to differentiate individuals with CMS from healthy Andean highlanders.